An Inductively-Coupled Plasma Electrothermal Radiofrequency Thruster - Tsifakis, Dimitrios; Charles, Christine; Boswell, Rod (Frontiers in Physics, 2020)
The “cubesat” form factor has been adopted as the defacto standard for a cost effective and modular, nano-satellite platform. Many commercial options exist for nearly all components re- quired to build such satellite; however, there is a limited range of thruster options that suit the power and size restrictions of a cubesat. Based on the prior work on the “Pocket Rocket” electro- thermal capacitively-coupled radiofrequency (RF) plasma thruster operating at 13.56 MHz, a new design is proposed which is based on an inductively-coupled radiofrequency plasma system operat- ing at 40.68 MHz. The new thruster design, which includes a compact and efficient radiofrequency matching network adjacent to the plasma cavity is presented, together with the first direct thrust measurements using argon as the propellant with the thruster immersed in vacuum and attached to a calibrated thrust balance. These initial results of the unoptimised first prototype indicate an up to 40% instantaneous thrust gain from the plasma compared to the cold gas thrust: typical total thrust at 100 SCCM of argon and 50 W RF power is ∼ 1.1 mN.